A Longitudinal Study of Recurrent Experience of Earthquake and Mental Health Problems Among Chinese Adolescents - Geng, Fulei; Zhou, Ya; Liang, Yingxin; Fan, Fang (Frontiers in Psychology, 2018)
Background: The effects of recurrent exposure to disasters on adolescents’ mental health have rarely been studied. We examined the effects of two earthquake experiences 5 years apart in a longitudinal cohort of Chinese adolescents. Methods: A total of 858 adolescents were assessed in September, 2011(3.5 years after the Wenchuan earthquake, 1.5 years before Ya’an earthquake, T1) and April, 2013 (one week after the Ya’an earthquake, T2). Participants’ Wenchuan earthquake experiences and symptoms of posttraumatic stress disorder (PTSD) and depression were assessed at T1, and their Ya’an earthquake experiences, Acute Stress Disorder (ASD), PTSD, and depression were assessed at T2. Results: Structural equation models showed a positive relationship between Ya’an earthquake experiences and symptoms of ASD, PTSD and depression at T2. T1 PTSD symptoms significantly increased T2 ASD, PTSD, and depression symptoms, and also mediated the relationships between Wenchuan earthquake experiences and T2 ASD, PTSD, and depression symptoms. T1 Depression symptoms also significantly increased T2 ASD, PTSD, and depression symptoms, but only mediated the association between Wenchuan earthquake experiences and T2 depression symptoms. In addition, Wenchuan earthquake experiences moderated the effects of Ya’an earthquake experiences on ASD symptoms and PTSD symptoms but not depression. Conclusions: Repeated to exposure to disasters have adverse additive effects on adolescents’ mental health. Adolescents who experience one disaster may be sensitive to the negative impact of subsequent ones.